Community skill & knowledge for tourism development - Aref, Fariborz; Redzuan, Ma’rof; Gill, Sarjit S. (Eurojournals, 2009)
The objective of this article is to assess the level of community skill and knowledge as wellas barriers of skill and knowledge in tourism development in Shiraz, Iran. It was found thatlevel of community skill and knowledge in the tourism development in local communitiesin low, especially in the modern district of Shiraz is lower than the old district. Regardingto this issue there are some barriers in terms of tourism development. It is the intention of this paper to bring to discussion barriers to skill and knowledge in tourism development. Inthis way, we review literature skill and knowledge and discuss the related barriers of skilland knowledge.